(untitled) (Revista Contexto & Saúde, 2026)
Objective: This is a methodological study aimed at the development and validation of six educational videos—considered educational technologies—on general and oral health for adolescents, using a mixed-methods approach. Methods: Participated in the research ten adolescents and ten specialists from the fields of Dentistry, Education, and Audiovisual Media. The research followed the methodology proposed by Teixeira and Mota (2011) and was conducted entirely online. It was carried out in ten structured steps, including the validation of both the script and the video using interviews and validating instruments. Results: The videos covered the following topics: dental caries, bullying, diseases transmitted by kissing, electronic cigarettes, oral piercings, and malocclusion. The scripts were evaluated by adolescents and specialists based on their aims, structure, rationale, organization, and writing style, all of which received approval ratings of 70% or higher. The videos were assessed for content, audiovisual quality, and character representation, with all criteria achieving approval ratings of 80% or higher from both groups. Feedback from interviews was used to improve the final versions of the videos. The average duration of the videos was 2 minutes and 4 seconds. Conclusion: The videos were found to be appropriate in terms of content accuracy, audiovisual quality, and character representation. Therefore, they are considered suitable for adolescents aged 13 to 18 years old. Educational technologies such as the videos developed in this study can be tools for the translation of scientific knowledge.